Plant quality of superior progenies in resin production of Pinus pseudostrobus LINDL. - Hernandez Ramos, Jonathan; Sáenz-Reyes, J. Trinidad; Chávez-García, Alicia Sagrario; Muñoz-Flores, H. Jesús; García-Magaña, J. Jesús; Gómez-Cárdenas, Martín (Ecosistemas y Recursos Agropecuarios, 2025)
In the propagation of plants in nurseries, it is important to define quality parameters to ensure their survival in the field. There is no evaluation of superior progenies in resin production in Michoacán, even though this economic activity is the most important in non-timber production. The objective was to generate plant quality parameters for dominant progenies at the site with resin production of Pinus pseudostrobus. In 2019, seed of 27 outstanding progenies in resin production was collected and five months after sowing they were transplanted into polyethylene bags and placed under the experimental design of random blocks with five repetitions, where the most vigorous individuals that represented the greatest number of individuals were included. potential. At 15 months after the transplant, the total height, basal diameter and biomass were evaluated, in addition, the slenderness indices, Dickson quality and lignification were calculated; intervals in plant quality indices or relationships were also determined. The analysis of variance and the Student-Newman-Keuls mean separation test show highly significant differences between the progenies (α = 0.01). The Llano 2 progeny is resistant to environmental effects, while Gómez 8 and Pascuala 9 have medium growth and more than 57.2 g biomass but are the most suitable for establishing plantations for resin production, given their morphological characteristics and plant quality indices. The plant quality indices generated and used in this study are easy to implement and interpret in forest nurseries for the identification of quality plants.